1996
DOI: 10.1055/s-0038-1650577
|View full text |Cite
|
Sign up to set email alerts
|

Increased Procoagulant Activity of Red Blood Cells from Patients with Homozygous Sickle Cell Disease and β-Thalassemia

Abstract: SummaryIt has recently been proved that, in vitro, red blood cells (RBCs) from patients with homozygous β-thalassemia behave as procoagulant cells. The procoagulant activity of β-thalassemia RBCs might be the result of an increased exposure of procoagulant phospholipids (i. e. phosphatidylserine) in the outer leaflet of the membrane. In order to test this hypothesis, we compared the catalytic properties of RBCs of patients with β-thalassemia and homozygous sickle cell disease (SS-RBCs) with that of controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 36 publications
8
94
0
4
Order By: Relevance
“…[57][58][59] A comparison of normal RBCs with those isolated from patients with ␤-TM or ␤-TI by our group suggests that thalassemic RBCs may provide a source of negatively charged phospholipids, which can increase thrombin generation, as measured by prothrombinase assay. 60,61 These results were confirmed in a similar assay using RBCs from splenectomized ␤-TI patients as a source of phospholipids. 19 The procoagulant effect of thalassemic RBCs seems to be due to an increased surface expression of anionic phospholipids such as phosphatidylethanolamine (PE) and phosphatidylserine (PS).…”
Section: Contribution Of Abnormal Thalassemic Rbcs To the Hypercoagulmentioning
confidence: 76%
See 3 more Smart Citations
“…[57][58][59] A comparison of normal RBCs with those isolated from patients with ␤-TM or ␤-TI by our group suggests that thalassemic RBCs may provide a source of negatively charged phospholipids, which can increase thrombin generation, as measured by prothrombinase assay. 60,61 These results were confirmed in a similar assay using RBCs from splenectomized ␤-TI patients as a source of phospholipids. 19 The procoagulant effect of thalassemic RBCs seems to be due to an increased surface expression of anionic phospholipids such as phosphatidylethanolamine (PE) and phosphatidylserine (PS).…”
Section: Contribution Of Abnormal Thalassemic Rbcs To the Hypercoagulmentioning
confidence: 76%
“…This was demonstrated by experiments that showed that annexin V, which binds anionic phospholipids, could block the procoagulant effect of isolated thalassemic RBCs. 61 These data suggest that the procoagulant effect of thalassemic RBCs may contribute to the hypercoagulable state in thalassemia by amplifying thrombin generation and initiating platelet activation.…”
Section: Contribution Of Abnormal Thalassemic Rbcs To the Hypercoagulmentioning
confidence: 84%
See 2 more Smart Citations
“…Perturbations in RBC PS exposure are seen as a pathogenic mechanism for the prothrombotic state of beta-thalassemia and sickle cell disease (37). Chronic uremia is associated with an increased risk of thrombotic complications, which may represent the predominant cause of mortality particularly in dialysis patients (38).…”
Section: Altered Composition Of the Erythrocyte Cell Membranementioning
confidence: 99%